Educating patients in stoma care. (2nd April 2019) - Bird, Andrew; Wilson, Kate; Bertinara, Ambra; Amos, Lyndsey
Abstract : Andrew Bird, Lead Stoma Care Nurse Specialist (andrew.bird@nuh.nhs.uk );Kate Wilson, Stoma Care Nurse Specialist;Ambra Bertinara, Stoma Care Nurse Specialist;Lyndsey Amos, Stoma Care Healthcare Assistant, all at Queen's Medical Centre, Nottingham University Hospitals NHS Trust, discuss education for new stoma patients